Pengendalian Kualitas Produk Batu Nisan di Kota Gresik dengan Pendekatan Seven Tools - Moh. Ririn Rosyidi; Narto Narto (Jurnal Optimalisasi, 2023)
In the Industrial Age 4.0, when business competition is increasing and growing, business people are also required to be able to maintain and increase their existence in products, This tombstone is one of the product needs when approaching the Idhul Fitri holiday because many people will replace the tombstones that have died or if a relative has passed away. Sadar Gresik UMKM produces tombstones and there is a defect problem that occurs, namely experiencing thin cracks and chipped corners of tombstones in April 2022 Sadar UMKM can produce an average of 41 gravestones in one day and for an average defect in 1 month 11 tombstones. In this study, aims to find out the quality control needed so that the tombstone products can control defects, by using the seven tools to find out the factors that cause defects and can control the defects by knowing the NP line on the control chart. Seven tools can also identify the causes and effects of defects and with the addition of 5W+1H recommendations will be made regarding the problems encountered. factors from the results of fishbone Diagrams that require evaluation which include human factors, materials, methods, environment where these factors cause the number of tombstone defects to be 174 thin cracks and tombstone corners to chip 121. To control defects in tombstone products so that at the midpoint of NP 11.8 is right at the midpoint of the control chart. From several factors that are already known in thin cracked tombstones, namely carrying out quality control of 5W + 1H tombstones, so that they can control these defects in accordance with predetermined product specifications/standards, the process of making tombstone products, employees who work on these have responsibilities, the need for training/skill training for the process of making the tombstones and monitoring the evaluation of the workers, the angle of the tombstones, namely carrying out quality control so as to minimize product defects, so that the quality produced is maintained according to the specified standards, the process of making tombstone products, employees those who do it have the responsibility, make repairs on a regular basis.